Application of Non-Linear Fiber Section Model on Spun Piles With and Without Concrete Infill Subjected to Cyclic Loading - Apriliana, Estu Ema; Irawan, Candra; Suprobo, Priyo (Journal of Civil Engineering, 2024)
This numerical analysis study predicts the behavior of spun piles with and without concrete infill under cyclic flexural loading and constant axial load. A fiber section using STKO pre- and post-processor for the OpenSEES program was employed. Spun piles were modeled using displacement-based beam-column elements with distributed plasticity and cyclic loading procedures with displacement control. The numerical method proposed for this research was verified by comparing it to reliable experimental results.